Modern asian design - Huppatz, D. J. (New York Bloomsbury Academic, 2018)
Modern Asian Design provides a comprehensive introduction to the development of Asian design in the modern period, both tracing historical threads and offering a theoretical framework within which to chart the history of design in Asia. Rather than a singular “Asian history”, this book presents a series of studies centred on trade routes, colonial relationships, regional networks and cross-cultural exchanges. Modern Asian Design builds on existing resources beyond design history in an effort to map the field, focusing particularly on relations between Asia and the West and also across Asian design cultures. Opening with a brief overview of trade and exchange networks in the 17th and 18th centuries, the bulk of this study comprises analysis of the development of modern design in Asia during the later 19th and early 20th centuries, a period of rapid modernisation. The book's final two chapters bring these central ideas into a contemporary and highly relevant context.--Provided by publisher.
Chapter 1: Foundations, 1700-1850 -- Chapter 2: Elite Paths -- Chapter 3: Colonial Paths -- Chapter 4: Professional Paths -- Chapter 5: Consumer Paths -- Chapter 6: Postcolonial Design and the State -- Chapter 7: Design and Development -- Chapter 8: The Design Professional -- Chapter 9: Globalization and Consuming Asian Design -- Conclusion
Keywords: Design -- Social aspects -- Asia